APPROACH AND PRINCIPLES RELATED TO TEACHING TEXT STRUCTURE IN MOTHER TONGUE CLASSES (American Journal of Pedagogical and Educational Research, 2023)
The article describes the methods and principles of teaching students to compose texts, and the methodology of teaching students to work on them and apply them in practice, were mentioned in the primary class mother tongue classes. This article focuses on the pedagogical approach and guiding principles associated with teaching text structure within mother tongue classes. Investigating how educators navigate the complexities of imparting textual comprehension and organization skills. This study provides a comprehensive exploration of the approach and principles related to teaching text structure in mother tongue classes. By drawing on metacognitive strategies, interactive methodologies, genre-based principles, cultural and linguistic considerations, and technology integration, the study contributes to a nuanced understanding of effective pedagogical practices for cultivating text comprehension skills within mother tongue education settings.